STUDI KASUS TENTANG SISWA YANG SULIT BERKOMUNIKASI DENGAN ORANG TUANYA PADA KELAS XI SMK N 1 PONTIANAK - Umaroh, Umaroh; Lestari, Sri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled case study about students who difficult to communicate with their parents in class XI SMK N 1 Pontianak. A common problem in this study is: How to solve problems students difficult to communicate with their parents in class XI SMK N 1 Pontianak?. The purpose of this study is to obtain an objective picture of a case study of students who are difficult to communicate with their parents in grade XI SMK N 1 Pontianak. The approach used in this study is qualitative using descriptive methods. The study form is a case study.data collection techniques used are direct observation, direct communication and home visits. Based on the result of observation and interview with the subject of the case concluded that the identification of student problems are the factor that cause difficult students to communicate with their parents are as follows: 1) internal factors of students are: a) mind, b) feelings, and c) emotion.2) external factors of students is the subject of the case is a child who is less active in social relationships with his family, especially with his parents, tend to be quiet in communicating. The alternatives of assistance provided are: 1) using the Transaktional Analysis counseling approach with empty seat technique, where this exercise aims to overcome interpersonal and intrapersonal conflict. 2) using the REBT counseling approach with reverse rational role exercises techniques, where the practice of this case subject plays a role to fight the irrational beliefs to be rational in the subject itself. Keywords: Case studies, communication difficulties